Risk factors for SARS-CoV-2 infection during the early stages of the COVID-19 pandemic: a systematic literature review - Harris, Matthew; Hart, John; Bhattacharya, Oashe; Russell, Fiona M. (Frontiers in Public Health, 2023)
Introduction: Identifying SARS-CoV-2 infection risk factors allows targeted public health and social measures (PHSM). As new, more transmissible variants of concern (VoC) emerge, vaccination rates increase and PHSM are eased, it is important to understand any potential change to infection risk factors. The aim of this systematic literature review is to describe the risk factors for SARS-CoV-2 infection by VoC. Methods: A literature search was performed in MEDLINE, PubMed and Embase databases on 5 May 2022. Eligibility included: observational studies published in English, after 1 January 2020; any age group; the outcome of SARS-CoV-2 infection; and any potential risk factor investigated in the study. Results were synthesized into a narrative summary with respect to measures of association, by VoC. ROBINS-E tool was utilised for risk of bias assessment. Results: Of 6197 studies retrieved, 43 studies were included after screening. Common risk factors included older age, minority ethnicity, low socioeconomic status, male gender, increased household size, occupation/lower income level, inability to work from home/public transport use, and lower education level. Most studies were undertaken when the ancestral strain was predominant. Many studies had some selection bias due to testing criteria and limited laboratory capacity. Conclusion: Understanding who is at risk enables the development of strategies that target priority groups at each of the different stages of a pandemic and helps inform vaccination strategies and other interventions which may also inform public health responses to future respiratory infection outbreaks. While it was not possible to determine changes to infection risk by recent VoC in this review, the risk factors identified will add to the overall understanding of the groups who are at greatest risk of infection in the early stages of a respiratory virus outbreak.